Ranking the Leading Risk Factors for Sudden Unexpected Death in Epilepsy - DeGiorgio, Christopher M.; Markovic, Daniela; Mazumder, Rajarshi; Moseley, Brian D. (Frontiers in Neurology, 2017)
Sudden Unexpected Death in Epilepsy (SUDEP) is rare in well-controlled epilepsy. However, SUDEP is a common cause of death in drug resistant epilepsy. Over the last 30 years, multiple cohort and population studies have identified clinical risk factors associated with an increased risk for SUDEP. In this review, SUDEP risk factors from major cohort and population-based studies are identified. We rank the leading SUDEP risk factors by Odds Ratios and Relative Risk Ratios. The incidence of SUDEP is also evaluated in special clinical situations, including antiepileptic drug treatment, epilepsy surgery, devices, and assignment to placebo in clinical trials. A ranking of the top risk factors could help clinicians identify patients at highest risk for SUDEP so that interventions could be individually tailored to reduce risk.